Cryo-EM analysis of PIP2 regulation in mammalian GIRK channels - Yiming Niu (eLife, 2020)
G-protein-gated inward rectifier potassium (GIRK) channels are regulated by G proteins and PIP2. Here, using cryo-EM single particle analysis we describe the equilibrium ensemble of structures of neuronal GIRK2 as a function of the C8-PIP2 concentration. We find that PIP2 shifts the equilibrium between two distinguishable structures of neuronal GIRK (GIRK2), extended and docked, towards the docked form. In the docked form the cytoplasmic domain, to which Gβγ binds, becomes accessible to the cytoplasmic membrane surface where Gβγ resides. Furthermore, PIP2 binding reshapes the Gβγ binding surface on the cytoplasmic domain, preparing it to receive Gβγ. We find that cardiac GIRK (GIRK1/4) can also exist in both extended and docked conformations. These findings lead us to conclude that PIP2 influences GIRK channels in a structurally similar manner to Kir2.2 channels. In Kir2.2 channels, the PIP2-induced conformational changes open the pore. In GIRK channels, they prepare the channel for activation by Gβγ.